The Absorption Rate Of Absorbable Sutures In Oral Surgery Patients - Titis Wicaksono Giman; Dendy Murdiyanto (CV. AFDIFAL MAJU BERKAH, 2026)
Absorbable sutures are a type of suture material that undergo degradation and are gradually absorbed by body tissues over a certain period, eliminating the need for manual removal. To provide an understanding of the absorption characteristics of absorbable sutures, which is essential for clinicians in selecting the most appropriate material for each oral surgical procedure. This study is a qualitative research in the form of a literature review using secondary data collected in April 2026 from three scientific databases: PubMed, ScienceDirect, and Scopus. Articles were retrieved from various online scientific journal sources using the keywords “absorbable sutures,” “absorption rate,” “oral surgery,” and “dental surgery sutures.” The absorption rate of absorbable sutures is a crucial factor influencing wound healing outcomes in oral surgical procedures. Unlike other body tissues, the oral cavity has a unique and more aggressive environment, characterized by high moisture due to saliva, the presence of various enzymes (proteases and esterases), fluctuations in pH and temperature, and a high level of microbial colonization. Fast-absorbing sutures, such as polyglactin, are suitable for mucosal tissues as they reduce inflammatory reactions and improve patient comfort. However, suture selection must still be tailored to the wound condition and the required tissue strength.